2020
DOI: 10.1364/oe.397051
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of silicon nanowire solar cells with a crescent nanohole

Abstract: In recent years, newly emerging photovoltaic (PV) devices based on silicon nanowire solar cells (SiNW-SCs) have attracted considerable research attention. This is due to their efficient light-trapping capability and large carrier transportation and collection with compact size. However, there is a strong desire to find effective strategies to provide high and wideband optical absorption. In this paper, a modified circular nanowire (NW) with a nanocrescent hole is newly introduced and analyzed for solar cell ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 50 publications
0
14
0
2
Order By: Relevance
“…The design using the axial junction which has been suggested gives a value of of 33.8 mA and a PCE of 18.5%. The efficiency achieved surpasses that of the asymmetric NW studied, with a crescent nanohole 34 with a volume reduction of 45%. Furthermore, the PCE of the NW suggested in the core–shell is equal to 19%, with an enhancement of 23% compared to the solid NW.…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…The design using the axial junction which has been suggested gives a value of of 33.8 mA and a PCE of 18.5%. The efficiency achieved surpasses that of the asymmetric NW studied, with a crescent nanohole 34 with a volume reduction of 45%. Furthermore, the PCE of the NW suggested in the core–shell is equal to 19%, with an enhancement of 23% compared to the solid NW.…”
Section: Introductionmentioning
confidence: 70%
“…Consequently, the (e–h) generated carriers in the thicker p-doped substrate layer have a higher probability of reaching the contacts. In this research, the dimension of the -doped back-surface-field (BSF) ( ) was taken as 400 nm 18 , 34 , which is smaller than the electron diffusion length thickness 48 . This layer helps in creating a barrier voltage for minority carrier recombination on the cathode Ag-metal contact 48 .…”
Section: Design Considerations and Numerical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have also shown that the light absorption could be further enhanced by introducing a single shell [19,20] or graded dual shells [21]. Recently, some new strategies have been performed to improve the light absorption in the NWs based on the symmetry breaking, such as opening crescent design [22,23], off-axial core-shell design [24,25], asymmetrical nanovoid design [14], partially capped design [26][27][28][29] and crescent nanohole design [30]. More recently, we investigated the symmetry-breaking structure from circular NWs to elliptical NWs [31].…”
Section: Introductionmentioning
confidence: 94%
“…Recently, some new strategies have been implemented to improve the lightharvesting capability of the NWs based on the symmetry breaking. For example, front (or rear)opening crescent design [33,34], off-axial core-shell design [35,36], asymmetrical nanovoid design [20], partially capped design [37][38][39][40], nanocone design [41][42][43][44], inclined design [45][46][47], disorder design [48][49][50][51][52] and crescent nanohole design [53]. More recently, we investigated the symmetry structure from circular NWs to elliptical NWs [54].…”
Section: Introductionmentioning
confidence: 99%